Pelatihan Penggunaan Prezi sebagai Media Pembelajaran Interaktif untuk Guru Sejarah SMA Se-Kota Pontianak - Andang Firmansyah; Kristoforus Bagas Romualdi; Eko Wahyu Junaidi; Astrini Eka Putri; Ika Rahmatika Chalimi; Mohammad Rikaz Prabowo; Yustinus Rudiyanto (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The main problem faced by history teachers is that historical materials are often perceived as abstract and less engaging, and many teachers are not yet accustomed to using digital media such as Prezi effectively. This training aimed to equip teachers with the skills to design engaging history learning materials that align with the characteristics of digital native students through the use of Prezi. The activity was conducted at Universitas Tanjungpura and involved 15 senior high school history teachers in Pontianak City who are members of the History MGMP, as well as pre-service teachers. The core workshop was held on September 20, 2025, using a training–practice–mentoring model that integrated conceptual delivery, hands-on practice, and technical assistance. The results showed a significant positive impact, as participants improved their understanding of digital native learning behaviors and their technical skills in operating Prezi. Teachers were able to present history materials in a more dynamic and interactive manner, reflecting the integration of technological and pedagogical knowledge (TPACK). Participants’ questionnaire responses also indicated very positive perceptions of the usefulness and quality of the training.